2019
DOI: 10.1155/2019/5942783
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Densitovolumetry Using Computed Tomography in Patients with Nontuberculous Mycobacteria: Correlation with Pulmonary Function Tests

Abstract: Background. Since nontuberculous mycobacterial pulmonary disease (NTM-PD) is a condition with increasing morbidity, a more detailed knowledge of radiological aspects and pulmonary function plays a relevant role in the diagnosis and appropriate therapeutic management of these patients. Objectives. The purpose of this study was to evaluate changes in lung parenchyma through computed tomography (CT) densitometry and, secondarily, to analyze its correlation with pulmonary function testing (PFT) in patients with NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In some patients who are difficult to treat by chemotherapy, surgical treatment should be considered. [ 20 , 36 ] Patients with NTM pulmonary diseases showed lower FVC and FEV 1 values than healthy controls, [ 37 ] and the disease severity can affect body weight and nutrition status. [ 38 ] In our study, the physical activity of patients with NTM pulmonary diseases might be related to skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients who are difficult to treat by chemotherapy, surgical treatment should be considered. [ 20 , 36 ] Patients with NTM pulmonary diseases showed lower FVC and FEV 1 values than healthy controls, [ 37 ] and the disease severity can affect body weight and nutrition status. [ 38 ] In our study, the physical activity of patients with NTM pulmonary diseases might be related to skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Upper lobes 14 Upper lobes 15 Nontuberculous mycobacterial disease LML, RML and RUL 16 Upper lobes 17 RUL, RML and LML 13 RUL, RML and LML 18 Primary ciliary dyskinesia RML, middle and lower lobes 19 LML 20…”
Section: Allergic Bronchopulmonary Aspergillosismentioning
confidence: 99%
“…The loss of lung mass volume is also a characteristic that is frequently identified among the radiological findings of patients with lung diseases. De Marca et al (2019) suggested that there is a relationship between mass and lung functions, however, this relationship is not yet fully elucidated 53 . Although all the findings described above are not specific towards a definitive NTM-LD diagnosis, it is described in the literature that the disease form with nodular infiltrates and bronchiectasis frequently affects the middle lobe and lingula regions 37,41 .…”
Section: Studies Bymentioning
confidence: 99%
“…The loss of lung mass volume is also a characteristic that is frequently identified among the radiological findings of patients with lung diseases. De Marca et al (2019) suggested that there is a relationship between mass and lung functions, however, this relationship is not yet fully elucidated 53 .…”
Section: Radiological Diagnosismentioning
confidence: 99%